Pepper Place Farmers' Market and the Need for Research and Strategy. (October 2019) - Anderson, Reynolds; Sheffield, Matthew; Smith, Joie C.; Carson, Charles M.; Eason, Clifton C.
Pepper Place Market, a farmers' market created in 1999 in Birmingham, Alabama, was designed as the centerpiece and foundation to support the long-term urban revitalization plan in Birmingham's historic Lakeview District. Cathy Jones, the founder and inspiration behind the market, began the market on land owned by her family's real estate company, Sloss Real Estate. The Pepper Place Market initially operated solely on cash flow received from farmers and artisans. In 2011, the market began soliciting sponsorships. The market's leadership wanted to expand the market but struggled with negative net income. The organization had no unified marketing strategy or marketing plan. The limited promotion in which Pepper Place Market engaged was inconsistent and lacked a clear, strong messaging. Realizing the market needed to do more, Jones believed conducting marketing research and creating a strategic marketing plan should be their next steps.